Antiaversive Effects of Cannabinoids: Is the Periaqueductal Gray Involved?. (1st December 2008) - Moreira, F. A.; Aguiar, D. C.; Campos, A. C.; Lisboa, S. F.; Terzian, A. L.; Resstel, L. B.; Guimarães, F. S.
Abstract : Cannabinoids play an important role in activity-dependent changes in synaptic activity and can interfere in several brain functions, including responses to aversive stimuli. The regions responsible for their effects, however, are still unclear. Cannabinoid type 1 (CB1) receptors are widely distributed in the central nervous system and are present in the periaqueductal gray (PAG), a midbrain structure closely involved in responses related to aversive states. Accordingly, exposure to stressful stimuli increases endocannabinoid (eCB) levels in the PAG, and local administration of CB1 agonists or drugs that facilitate eCB-mediated neurotransmission produces antinociceptive and antiaversive effects. To investigate if these drugs would also interfere in animal models that are sensitive to anxiolytic drugs, we verified the responses to intra-PAG injection of CB1 agonists in rats submitted to the elevated plus-maze, the Vogel punished licking test, or contextual aversive conditioning model. The drugs induced anxiolytic-like effects in all tests. The same was observed with the transient receptor potential vanilloid type 1 (TRPV1) antagonist capsazepine and with cannabidiol, a nonpsychotomimetic phytocannabinoid that produces anxiolytic-like effects after systemic administration in humans and laboratory animals. These results, therefore, suggest that the PAG could be an important site for the antiaversive effects of cannabinoids.